2 + 2 =
4 + 5 =
6 + 4 =
Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
1: =1/8*9/4=9/32
2: =8/27*243/32=9/4
3: =(5/4*4/5)^5*(4/5)^2=16/25
4: \(=\left(-\dfrac{5}{6}\cdot\dfrac{6}{5}\right)^2\cdot\left(\dfrac{6}{5}\right)^2=\dfrac{36}{25}\)
5: \(=\left(-\dfrac{4}{3}\right)^3\cdot\left(\dfrac{3}{4}\right)^{10}=\left(-1\right)\left(\dfrac{3}{4}\right)^7=-\left(\dfrac{3}{4}\right)^7\)
6: \(=\left(\dfrac{1}{3}\cdot\dfrac{-9}{2}\right)^4\left(-\dfrac{9}{2}\right)^2=\left(-\dfrac{3}{2}\right)^4\cdot\dfrac{81}{4}=\dfrac{9}{4}\cdot\dfrac{81}{4}=\dfrac{729}{16}\)
8: =(0,2*5)^4*5^2=25
10: =-0,5^5*2^10
=-0,5^5*2^5*2^5
=-32
13: =(0,5*2)^2*2^2=4
Sửa đề: 3^5+3^5+3^5; 2^x
=>\(2^x=\dfrac{4^5\cdot4}{3^5\cdot3}\cdot\dfrac{6^5\cdot6}{2^5\cdot2}\)
=>\(2^x=\left(\dfrac{4}{3}\right)^6\cdot\left(\dfrac{6}{2}\right)^6=4^6=2^{12}\)
=>x=12
\(9+2+5+3+7+8+4+2+9+6+4+65+6+7+4+6+3+7+4+8+5+9+08+87+1+2+3+4+2+3+2+5+6+767+5+75+6+4+6+5+66+5+7+546+46+43+6+3+6+4+6+7+8878+68+68+6+7+9+9=10961\)
b) Tính theo thứ tự từ trái sang phải.
4 + 5 - 7 = 2 6 - 4 + 8 = 10 10 - 9 + 6 = 7 9 - 4 - 3 = 2
1 + 2 + 6 = 9 3 + 2 + 4 = 9 8 - 2 + 4 = 10 8 - 4 + 3 = 7
3 - 2 + 9 = 10 7 - 5 + 3 = 5 3 + 5 - 6 = 2 2 + 5 - 4 = 3
2) -3(4 - 7) + 5(-3 + 2)
= -3.4 + 3.7 - 5.3 + 5.2
= -12 + 21 -15 + 10
= 31 - 27
= 4
4) -5(2 - 7) + 4(2 - 5)
= -5.2 + 5.7 + 4.2 - 4.5
= -10 + 35 + 8 - 20
= 38 - 30
= 8
3: \(=20-12-8+12=20-8=12\)
5: \(=-18-42-21-35=-116\)
3: \(=-15+18-12+8=-27+26=-1\)
2: \(=-12+21-15+10=9-5=4\)
2+2=4
4+5=9
6+4=10
2 + 2 = 4
4 + 5 = 9
6 + 4 = 10